Hydrochemical Characteristics and Genetic Analysis of Shallow High-Fluorine Groundwater in Fuyang River Basin. (16th May 2022) - Zhai, Zhiwei; Zhang, Chuanda; Tang, Tiansong; Zhang, Chunyan; Bao, Xing; Li, Kunchao; Han, Bo
Abstract : In order to understand the sustainable and effective utilization of groundwater resources in Fuyang River Basin, the chemical characteristics and genetic evolution process of characteristic shallow fluoride groundwater in the region were carried out. The results show that the chemical characteristics of groundwater are zonal in horizontal direction. From the piedmont plain to the central plain, the hydrochemical types of the first and second aquifers are mainly HCO3 -Ca-Mg-type water, HCO3 -Cl-Ca-Mg-type water, Cl-SO4 -Na-Ca-type water, and Cl-SO4 -Na-Mg-type water. The main mineral sources of hydrochemical ions are salt rock, carbonate rock, sulfate rock, and silicate rock. F - has a significant positive correlation with HCO3 - while it is negatively correlated with K + . In the strong evaporation and alkaline environment created by climatic conditions in the study area, F - mainly comes from the dissolution of minerals. Gypsum and fluorite are in a relatively stable dissolved state continuously providing F - and Ca 2+ for groundwater; the adsorption of cation was gradually strengthened from the piedmont plain to the central plain. The high HCO3 - content is also conducive to F - desorption in alkaline environments. The samples with F - concentration greater than 1 mg·L -1 accounted for 35.7% and mainly distributed in the south of the study area. In summary, the chemical characteristics of shallow groundwater in Fuyang River Basin are affected by the combined effects including leaching effect, evaporation concentration, ion exchange-desorption, and human factors.